Intra-seasonal variation of anthropometrical, conditional, and technical tests in U14 soccer players. [Variación en los parámetros antropométricos, condicionales y test técnicos de jugadores de fútbol SUB-14]. - Fabio Massimo Francioni; Antonio José Figueiredo; Corrado Lupo; Marco Terribili; Giancarlo Condell; Antonio Tessitore (Ramón Cantó Alcaraz, 2018)
This study aimed to analyze the annual variation of soccer players abilities assessed by means of a field-battery test administered six times during an entire competitive season (from T0 to T5). Anthropometric (i.e., body mass, stature, and body mass index), soccer skill (i.e., touch with the body, touch with the head, passing, shooting, dribbling with pass, and dribbling) and functional capacities (i.e., counter-movement jump with and without free arms, and speed) tests were submitted to 33 Under-14 soccer players. A general improvement across the season as confirmed by the rising effects from 0.3 (T2) to 0.6 (T5) was showed. The technical skills (except touch with the head and dribbling) and functional tests showed significant differences (p < 0.001) between T0 and T5 but they were not dependent by the exposure to training. This study underlined that the skills' development in youth soccer players are not linear due to the effects of the growth and maturation. In order to optimize this process, in-season assessment are needed. Finally, programs and decisions promoted by coaches and scouts aimed to the development of youth soccer players should be inspired by the potential results that might be achieved by players. Resumen El objetivo del presente estudio consistió en analizar la variación anual de las habilidades de jugadores de fútbol sub-14 (n=33) mediante una batería de test de campo administrados seis veces a lo largo de la temporada (de T0 a T5). Las mediciones registradas se centraron en aspectos antropométricos (i.e., talla, peso e índice de masa corporal), habilidades específicas (i.e., toques con el cuerpo, con la cabeza, pases, lanzamientos, regates con pase y regates) y la condición física (i.e., salto en contra movimiento con y sin movimiento de brazos y velocidad). Los resultados mostraron una mejora a lo largo de la temporada con efectos que pasaron de 0.3 (T2) a 0.6 (T5). Las habilidades técnicas (excepto el toque con la cabeza y el regate) y los test funcionales mostraron diferencias significativas (p<0.001) entre los periodos T0 y T5, pero éstas no fueron dependientes de la exposición al entrenamiento. El presente estudio permite resaltar que el desarrollo de habilidades en jóvenes jugadores de fútbol no es lineal debido a los efectos del desarrollo y la maduración. En relación con el proceso de optimización de entrenamiento se requieren evaluaciones a lo largo de la temporada. Finalmente, los programas específicos y las decisiones de entrenadores y scouters debe centrarse en el desarrollo de los jugadores jóvenes tomando como punto de partida el potencial que pueden alcanzar.